Key technical factors for elite 50 m rifle 3 positions shooting performance - Lang, D.; Wang, F.; Wang, N.; Yang, T. (Sports Biomechanics, 2024)
The purpose of this study was to analyse the differences on the shooting score and shooting technical parameters with 50 m rifle three positions, and to find the key technical factors of shooting performance in international-level 50 m rifle shooters. A SCATT MX-02 optoelectronic shooting test system was used to collect shooting score and shooting technical variables. There was a significant effect of shooting position in shooting performance, aiming accuracy, stability of hold, stability of triggering (ANOVA, position, p < 0.05). PCA identified four principal components from 8 shooting technical variables, namely stability of hold, aiming accuracy, stability of triggering and aiming time. PCR indicated that these four components were able to account for 67.1% of the variance in standing shooting, 75.9% in kneeling, and 80.2% in prone. From these, the aiming ability was the most important component, which could explain 28.5% of the variance in standing shooting, 38.4% in kneeling, and 33.8% in prone. With the help of optoelectronic training system, these components should be in focus by coaches and athletes when conducting tests and training.